Action of the interaction cinetina, butyric acid and gibberellic acid on the initial growth and flowering of sunflower - Santos, Carlos Alan Couto dos; Peixoto, Clovis Pereira; Vieira, Elvis Lima; Carvalho, Everton Vieira; Peixoto, Vicente Américo Barbosa (Comunicata Scientiae, 2012)
The aim of this study was to evaluate the action of plant biostimulant Stimulate® on early growth and flowering of sunflower (Helianthus annuus L.). The experiment was conducted in the greenhouse and in the laboratory of the Center for Environmental and Biological Agricultural Sciences (CCAAB), Federal University of Bahia State Recôncavo. It was used sunflower seeds, cultivar Catissol 01 and biostimulant plant Stimulate® (0,009 % kinetin, 0,005 % butyric acid and 0,005 % gibberellic acid ). The treatments were: T1 = control (plants originated from seeds without any treatment - CT), T2 = plants originated from seeds pre-soaked in water (EA), T3 = plants originated from seeds pre-soaked in solution Stimulate® (ES), T4 = plants originated from seeds pre-soaked in water and sprayed with water (E+P/A), T5 = plants sprayed with water (PA), T6 = plants originated from seeds pre-soaked in solution Stimulate® (4 mL L-1) and then sprayed with solution Stimulate® (E+P/S), T7 = plants treated with Stimulate® solution (PS). The sowing was carried out in polyethylene bags (capacity 2 kg) containing commercial substrate. At 9, 13 and 16 days after sowing (DAS) foliar sprays were performed. At 32 DAS it was evaluated: the total length of plant and total dry mass, and at 30 and 32 DAS compared the phenological stages of plants. The design was completely randomized design with seven treatments and eight repetitions. Data were subjected to analysis of variance and treatment means, Tukey’s test at 5 % probability error. The combination of pre-soaking seeds, plus the subsequent foliar spraying with Stimulate® (E+P/S) was more efficient on growth and promoted earlier flowering sunflower.